Konjugat Poliklonal Antibodi Nanopartikel Emas untuk Deteksi Potato Virus Y - Ifa Manzila; Tri Puji Priyatno; Fikri Hidayatullah (Jurnal Fitopatologi Indonesia, 2020)
Polyclonal Antibodi-Gold Nanoparticles for Potato Virus Y Detection Gold nanoparticles are stable colloidal solutions with dimensions of 1-100 nm having surface plasmon resonance with six free electrons. The existing of six free electrons on the surface of a plasmon causes gold nanoparticles to bind easily to various types of bioreseptors including polyclonal antibodies. Polyclonal potato virus Y (PVP) antibodi been successfully conjugate with gold nanoparticles in order to develop a rapid detection for PVY infection in potato plants. The gold nanoparticles was synthetized by the reduction of gold (III) chloride trihydrate (HAuCl4) with 1% sodium citrate. Subsequently, the nanoparticles were used to make gold nanoparticle-antiobody PVY-conjugate. PVY detection was carried out with dot blot method on the nitrocellulose membrane. The results showed that the PVY virus on the membrane can be detected 10-30 minutes after incubation, depend on the concentration of the conjugate and the concentration of the virus in the sampel. The use of gold nanoparticle conjugates can increase the efficiency of the immunodot blot method in about 1 hour, and this method can be developed to be a lateral flow system for field detection of PVY.